2006
DOI: 10.1007/bf03021823
|View full text |Cite
|
Sign up to set email alerts
|

Acute diastolic dysfunction in thoracoabdominal aortic aneurysm surgery

Abstract: Purpose: To report transesophageal echocardiographic (TEE) findings consistent with intraoperative acute diastolic dysfunction in a series of patients undergoing thoracoabdominal aortic aneurysm (TAAA) repair.Methods: A series of nine consecutive patients underwent TAAA repair with intraoperative TEE monitoring. Surgical repair was performed with the adjunct of a left atrio-femoral bypass. Invasive arterial and venous pressures were monitored. Intraoperative TEE was utilized to assess the diastolic function be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 15 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…18 Using transesophageal echocardiography, Fayad et al demonstrated acute diastolic dysfunction upon aortic cross clamping in two thirds of patients undergoing TAAA repair. 20 Thus, the presence of coronary artery disease, valvular function, and overall heart function should be assessed preoperatively, 21 and if possible, significant cardiac issues should be corrected before surgery. Pulmonary.…”
Section: Discussionmentioning
confidence: 99%
“…18 Using transesophageal echocardiography, Fayad et al demonstrated acute diastolic dysfunction upon aortic cross clamping in two thirds of patients undergoing TAAA repair. 20 Thus, the presence of coronary artery disease, valvular function, and overall heart function should be assessed preoperatively, 21 and if possible, significant cardiac issues should be corrected before surgery. Pulmonary.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, preoperative DD was found to be a significant marker of in-hospital mortality after cardiac surgery and is independent of systolic function or the type of cardiac procedure [113]. Intraoperative acute DD is a new entity, which was observed by our research group during thoracoabdominal aortic aneurysm surgery [114]. In that study, postoperative myocardial infarction was significantly higher in patients who developed intraoperative acute DD.…”
Section: Isolated Systolic Hypertension As a Perioperative Cardiovascmentioning
confidence: 98%
“…62 Fayed et al reported acute diastolic dysfunction after high aortic clamping in six of nine patients with normal E/A ratios before clamping in thoracoabdominal surgery and three of those patients developed myocardial infarction. 63 The level of aortic cross clamp again has an influence on diastolic dysfunction and its effect on outcome.…”
Section: Aortic Cross-clampingmentioning
confidence: 99%